How To Make a Treefrog House - Monica E. McGarrity; Steve A. Johnson (EDIS)
WEC-263, a 3-page illustrated fact sheet by Monica E. McGarrity and Steve A. Johnson, provides simple instructions for children to make, decorate and monitor a treefrog house. Published by the UF Department of Wildlife Ecology and Conservation, June 2009.